Ashkenazim and Sephardim: Language Miscellanea - Katny, Andrzej; Olszewska, Izabela; Twardowska, Aleksandra (Sprach- und Kulturkontakte in Europas Mitte, 2019)
The collection of articles chosen by the editors presents a broad variety of issues connected with Jewish languages (Judeo-Spanish, Yiddish) and co-territorial languages used by Ashkenazi and Sephardic Jews in different places and periods. Thus, the book contains both strictly linguistic and sociolinguistic descriptions (including the aspects of evaluating language, language in contact or linguistic identity), the presentation of languages in literary works (and their translations) from different periods, as well as lexicographical and cultural observations. This thematic variety shows opportunities for the research into the languages of both Jewish groups and inspires other scientific projects in this field.